2012
DOI: 10.1111/j.1360-0443.2011.03771.x
|View full text |Cite|
|
Sign up to set email alerts
|

Topiramate for the treatment of methamphetamine addiction: a multi‐center placebo‐controlled trial

Abstract: Aims Topiramate has shown efficacy at facilitating abstinence from alcohol and cocaine abuse. This double-blind, placebo-controlled outpatient trial tested topiramate for treating methamphetamine addiction. Design Participants (N=140) were randomized to receive topiramate or placebo (13 weeks) in escalating doses from 50 mg/day to the target maintenance of 200 mg/day in weeks 6–12 (tapered in week 13). Medication was combined with weekly brief behavioral compliance enhancement treatment. Setting The trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 17 publications
2
72
0
2
Order By: Relevance
“…Several studies examining drug-use severity, for example, have identified frequency of use at treatment entry to be an important factor that affects treatment response (Simpson et al, 2002;Vaillant, 1988). Recent studies with clinical samples of MAdependent users also support the importance of considering MA-severity when examining posttreatment outcomes, since heavy or daily use is considered to increase one's risk for relapse (Brecht and Herbeck, 2014;Elkashef et al, 2008Elkashef et al, , 2012Heinzerling et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies examining drug-use severity, for example, have identified frequency of use at treatment entry to be an important factor that affects treatment response (Simpson et al, 2002;Vaillant, 1988). Recent studies with clinical samples of MAdependent users also support the importance of considering MA-severity when examining posttreatment outcomes, since heavy or daily use is considered to increase one's risk for relapse (Brecht and Herbeck, 2014;Elkashef et al, 2008Elkashef et al, , 2012Heinzerling et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Topiramate is efficacious for treating smoking addiction in men, but not women (Anthenelli et al, 2008). It has very limited efficacy in treating methamphetamine addiction (Elkashef et al, 2012;Ma et al, 2013). Thus, although the mechanism by which topiramate treats substance use disorders is not entirely clear, it appears to be one of the better clinical tools available for treating addiction.…”
mentioning
confidence: 99%
“…A multisite outpatient trial of topiramate 200 mg for reducing meth use was negative for the primary outcome. However, there was a positive effect in the subgroup of patients that had negative urines at randomization suggesting a role in relapse prevention (Elkashef et al 2012). Vigabatrin (GVG) was tried in an open-label study of 30 for 9 weeks.…”
Section: Gaba Agonistsmentioning
confidence: 99%